Detection of Power Quality Disturbances in Micro Grid Connected Power System - Priyadharshini K.M; S. Srinivasan; C. Srinivasan (Institute of Advanced Engineering and Science, 2015)
Micro Grid is a contracted distributed AC or DC network. Micro Grid resources are connected to the distributed linear as well as nonlinear loads through power electronics converter to provide an efficient, more reliable and quality power to the distributed loads with reduced co2 emission. Consequently makes full use of low cost generation resources and reduce waste. Interconnected Mode in the MG is connected to main grid either being absorbed by it or injecting some amount of power into the main system. Islanding Mode in the MG operates separately when upstream volt occurs in main grid network. Usage of power electronic interface converters, Integration of the renewable-resources based MG system to the main power system and nonlinear loads results in harmonics generation clutter the system reliability and other associated quality issues. Most of demanding users of electricity are suffering to a certain poor quality of electrical power. The excellent time-scaling resolution characteristic of WT used for detection of various power quality disturbances of integrating and islanding Micro Grid connected Distributed Generation systems. The WT plays important role in analysis, design and classification of discrete signal processing. The accuracy and reliability of classification techniques have assessed on signals contaminated with noise. DOI: http://dx.doi.org/10.11591/telkomnika.v14i1.7232